Frameworks for the design and reporting of anaesthesia interventions in perioperative clinical trials - Karen D. Coulman; Lucy Elliott; Natalie S. Blencowe; Joyce Yeung; Leila Rooshenas; Robert J. Hinchliffe; Ronelle Mouton; Eric Albrecht; David Bosanquet; Kariem El-Boghdadly; Gudrun Kunst; Mandeep Phull; et al. (BJA Open)
Background: Interventions from RCTs can only be replicated and implemented if reported in sufficient detail. This study developed frameworks to assist researchers with describing, monitoring, and reporting the key components of anaesthetic interventions in trials. Methods: This study comprised three phases: (1) initial framework development—text describing the delivery of anaesthetic interventions was coded and categorised into components using thematic analysis; (2) refinement of frameworks—facilitated structured group discussions were conducted with perioperative clinicians, researchers, and journal editors to elicit additional framework categories and consider clarity and feasibility; (3) framework testing and further refinement—cognitive interviews with professionals undertaking trials evaluating anaesthesia interventions to test the feasibility of using the frameworks in contemporary perioperative trials. Results: Three frameworks were developed for general, regional, and sedation anaesthesia interventions. Data saturation of categories within the frameworks was reached after inclusion of 15 RCTs for general and regional anaesthesia, and 13 for sedation. Each framework is structured into three main sections: (1) professional(s) delivering the intervention; (2) setting; and (3) intervention components, with descriptions of the preoperative, intraoperative, and postoperative stages unique to each anaesthetic intervention. Each framework deconstructs an anaesthetic intervention into component parts to support researchers with the design and reporting of RCTs. Final frameworks are available at: https://anaesthesiaframeworks.blogs.bristol.ac.uk/. Conclusions: We provide novel frameworks to be used during the design of perioperative trials to facilitate the design, delivery, and reporting of anaesthesia interventions.